Intranasal administration of stem cell-derived exosomes for central nervous system diseases - Gotoh, Shuho; Kawabori, Masahito; Fujimura, Miki (Neural regeneration research, 2024)
Abstract Exosomes, lipid bilayer-enclosed small cellular vesicles, are actively secreted by various cells and play crucial roles in intercellular communication. These nanosized vesicles transport internalized proteins, mRNA, miRNA, and other bioactive molecules. Recent findings have provided compelling evidence that exosomes derived from stem cells hold great promise as a therapeutic modality for central nervous system disorders. These exosomes exhibit multifaceted properties including anti-apoptotic, anti-inflammatory, neurogenic, and vasculogenic effects. Furthermore, exosomes offer several advantages over stem cell therapy, such as high preservation capacity, low immunogenicity, the ability to traverse the blood-brain barrier, and the potential for drug encapsulation. Consequently, researchers have turned their attention to exosomes as a novel therapeutic avenue. Nonetheless, akin to the limitations of stem cell treatment, the limited accumulation of exosomes in the injured brain poses a challenge to their clinical application. To overcome this hurdle, intranasal administration has emerged as a non-invasive and efficacious route for delivering drugs to the central nervous system. By exploiting the olfactory and trigeminal nerve axons, this approach enables the direct transport of therapeutics to the brain while bypassing the blood-brain barrier. Notably, exosomes, owing to their small size, can readily access the nerve pathways using this method. As a result, intranasal administration has gained increasing recognition as an optimal therapeutic strategy for exosome-based treatments. In this comprehensive review, we aim to provide an overview of both basic and clinical research studies investigating the intranasal administration of exosomes for the treatment of central nervous system diseases. Furthermore, we elucidate the underlying therapeutic mechanisms and offer insights into the prospect of this approach.